Propuesta para el mejoramiento del servicio al público en general mediante un sistema de responsabilidad social empresarial en la cooperativa de transporte Carlos Alberto Aray. - Iza Lluilema, Jaime Andrés (2019)
The following research is based on the corporate social responsibility system for the public service in “Cooperativa De Transporte Carlos Alberto Aray”. To develop the system, there was a previous diagnosis to determine in which situation is the transport company. It was needed the ISO 26000 standard in order to evaluate the system to improve it, taking into account that the service has a deficit in its Customer Support. There are some complaints as that clients claims as; loss of luggage, parcels do not reach to their destination, the company does not have the adequate infrastructures, lack of trained personnel, users demand greater security, lack of information from the cooperative about shifts. Those drawbacks have caused problems to satisfy people´s needs whom use this transport. The main objective of this project is to provide better service, to achieve will need surveys, interviews, ground research, Ishikawa and 80-20 plot. The contribution that will provide the corporate social responsibility system are trainings, will improve the work environment, the ethics of the transport company, will decrease the pollution, will take care of the welfare of its collaborators, you will get profits, will encourage social assistance as a result of having motivated workers. They will provide better service to the clients. The beneficiaries of the project are the workers staff located in each province, drivers, drives assistance, affiliates, the users and the general public.